INFLUENCE OF SURROGATE ADVERTISING ON BRAND AWARENESS AND PERCEPTION AMONG YOUNG ADULTS IN INDIA: AN ANALYSIS OF AWARENESS AND ETHICAL CONSIDERATIONS - Riwaria, Sonia; Shah, Mamta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the influence of surrogate advertising on brand awareness and perception among young adults aged 20-25 in India. Surrogate advertising, commonly used to promote restricted products such as alcohol and tobacco indirectly, is increasingly prevalent in the Indian market. Through a cross-sectional survey of 300 respondents, this research examines awareness levels, attitudes, and purchase intentions regarding brands employing surrogate advertising tactics. The findings reveal a high level of awareness of surrogate advertising strategies, particularly for alcohol-linked brands, with a significant positive correlation between awareness and favorable brand perception. Additionally, factors such as educational background and frequent social media use were associated with higher recognition of surrogate advertising. Interestingly, ethical concerns about surrogate tactics appeared to have minimal influence on brand perception among participants, suggesting a gap in critical awareness of indirect advertising strategies. These insights underscore the need for media literacy initiatives and regulatory measures to ensure young adults make informed brand choices. This study contributes to the literature on advertising ethics and consumer awareness in restricted product categories, offering implications for policymakers and marketers alike.